Comparability of Measurement of Astigmatism between URk-800F Auto Refracto-keratometer and MS-39 Anterior Segment Optical Coherence Tomography in Patients with Refractive Error - Gupta, Namrata; Maharjan, Samrina; Sapkota, Suman (Nepalese Journal of Ophthalmology, 2023)
Introduction: Accurate refractive error assessment is the first and the most important step of ocular examination. A reliable screening method of refractive status is important for early detection and prevention of blinding complications of uncorrected refractive error. Objectives: To evaluate the comparability of astigmatism measured by an auto-refractometer (URk-800F) with the measurements of the gold standard anterior segment optical coherence tomography (AS-OCT). Materials and methods:This cross-sectional observational study was conducted in a tertiary eye centre in Kathmandu from February 2023 to June 2023. A total of 100 patients with best corrected visual acuity of ≥ 20/20, spherical refractive error with cylindrical error of more than and equal to -0.75 and no pathology detected on slit lamp examination were taken by consecutive sampling method. Ethical approval was taken for the study. The data were entered into Microsoft Excel and analysed using Bland-Altman analysis. Results: The mean cylindrical power and axis was -2.33 D and 88 degrees for the right eye and -2.32 D and 122 degrees for the left eye respectively, as measured by MS-39 AS-OCT. For URK 800-F Auto-refracto Keratometer, the mean cylindrical power and axis was -2.31 D and 89 degrees for the right eye and -2.27 D and 124 degrees for the left eye. Conclusion: The findings of this study conclude that an auto-refractometer can be used as an effective tool for identification of spherical refractive error as well as measurement of accurate cylindrical power and cylindrical axis in low resource primary care settings.